Reliable JavaScript - Spencer, Lawrence D.; Richards, Seth H. (Wrox professional guides, 2015)
Create more robust applications with a test-first approach to JavaScript Reliable JavaScript, How to Code Safely in the World's Most Dangerous Language demonstrates how to create test-driven development for large-scale JavaScript applications that will stand the test of time and stay accurate through long-term use and maintenance